'Great deal' belongs in dog food - Pappas, Mike (Raton, NM Raton Range, 1990)
Columns written by Mike Pappas, owner of the Sweet Shop Restaurant, for the Raton Daily Range on a wide variety of topics, some historical, some current, some personal.
Newspaper Article by Mike Pappas
Master list item #: 143
File location is in the Raton File Cabinet
Keywords: Pappas, Mike; Life and Customs; Local History; Holiday Parties; Rib-Eye Steaks; Restaurant; Raton, New Mexico